Research on measuring the capacity of a UV-disinfectant machine by disinfecting masks used by Covid-19 infected patients - Suchona, Sanjida Akter (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.